(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
This article is one of the research results devoted to the study of the systematics, geographical distribution and bioecology of the species of Sassik carpet, which have been acclimatized in the territory of our Republic in the last century, have medicinal and food value. The root of this plant is the flower stem and The body of the fruit has healing properties. The substance in its juice contains substances with high physiological activity.